Farm worker uprising in the Western Cape: a case study of protest, organising, and collective action - Wilderman, Jesse (My University, 2015)
This research report looks at the historic farm worker strikes and protests that took place during late 2012 and early 2013, involving thousands of farm workers and the rural poor in the Western Cape, with a view to answering: 1) why did the protests take place when they did; 2) how did the protests spread across the Western Cape; and 3) did the mass participation of the protests turn into formal organisation. The research was conducted primarily through in-depth interviews with participants and observers of the protests during field visits to the Western Cape in late 2013 and early 2014. The findings of the report suggest that farm owners, responding to top-down pressures of shifting global production standards and competition, along with increased government regulation and worker protections, continue to move toward a more seasonal, outsourced, and off-farm labour force; the transformation of the workforce is leading to a breakdown or re-negotiation of two of the major impediments to overt, confrontational, and collective action, namely paternalistic social construction and farm worker isolation. These longer-term trends combined with the spark of a small, successful strike and an increasing sense of tactics, strategy, and possibility to ignite a large-scale strike in one of the major farming towns in the area. With the help of television coverage featuring scenes of this protest and a clear demand by protestors themselves for an increase in the minimum wage, local organisations then served as “coordinating” units, alongside a range of more informal networks, to spread the protest and its easily replicable tactics to towns around the region. In part because farm workers do not have meaningful access to the more institutional vehicles for expressing their grievances, the protests took on a more bottom-up, “spontaneous” nature and spread, with the strategy of disruption and its emerging repertoires of contention serving as key sources of power. Because of the unique nature of the protests and the shifting nature of farm worker identities, most of the participating organisations were unsuccessful at translating the mass participation of the protests into greatly expanded levels of formal organisation. This challenge of turning participation into organisation was exacerbated by a major backlash by farm owners after the protest, as well as by some of the organising approaches of these organisations during and after the protests. The report concludes that there may be reasons for hope as the protests seem to have created some expanded confidence and leadership among farm workers, even if they did not primarily challenge power on the farms; the question remains as to whether this historic uprising can lead to further transformation from below.
Research Report Global Labour University, Department of Sociology University of Witwatersrand, Johannesburg September 26th, 2014
Keywords: Agricultural laborers--South Africa--Western Cape; Agricultural laborers--Labor unions--South Africa; Labor market--South Africa